KASTRASI FREKUENSI PUBLIK: MEDIA LITERACY ERA BUDAYA POPULER - YULIANA RAHMAWATI (Jurnal Komunikasi, 2015)
Civilization change is a necessity. Culture as one formers also experienced dynamic civilization. Changes in form and content (content ) takes place not in a vacuum but in a variety of contextual quadrants. The era of modernity with the development of industry and capitalism climate has led to one part in cultural homogenization. Public spaces which in essence is a classless into an entity that has a value of commodities. Shift function of public spaces including public frequency in packs of popular culture has been a challenge for the creation of the public who have media literacy skills. With media literacy, public to understand what has been done for the public media and to the public .Keywords : public frequency , media literacy, cultural homogeneity, Castration